Peran Kegiatan Ekstrakurikuler Keagamaan dalam Penguatan Karakter Kepemimpinan Siswa di SMK Umar Zahid Semelo Jombang - Ai'sya Novitasari; Dian Kusuma Wardani; Nanang Qosim (Lembaga Yasin AlSys, 2026)
Although the development of adolescent leadership character is increasingly important in addressing moral decline, juvenile delinquency, and the weakening practice of religious values, studies that specifically connect religious extracurricular activities with students’ leadership character still need to be strengthened. This study aims to describe the implementation of religious extracurricular activities, namely Khotmil Qur’an, Al-Banjari, and Management Qolbu, and to analyze their relationship with students’ leadership character at SMK Umar Zahid Semelo. This study used a quantitative approach with a correlational design, involving 95 students from classes X-A, X-C, and X-D selected through purposive sampling. Data were collected using a validated Likert-scale questionnaire and were then analyzed using the Pearson Product Moment correlation test. The results showed a positive and significant relationship between students’ participation in religious extracurricular activities and the development of leadership character, with a correlation coefficient of 0.690, which falls into the strong category. Students who actively participated in religious extracurricular activities demonstrated better morality, integrity, discipline, responsibility, and leadership skills. These findings confirm that religious extracurricular activities have a strong relationship with the strengthening of students’ leadership character. The implications of this study contribute to the development of character education in vocational high schools and serve as a practical reference for schools in optimizing religious extracurricular programs as a strategy for fostering students’ character and leadership.